Analisis Sistem Rantai Pasok Farmasi: Evaluasi Kepatuhan Prosedural Penerimaan Logistik dan Implikasinya terhadap Patient Safety di Apotek Kota Makassar - Irfan Kurniawan; Asyari Al Hutama; Salwah Suardi; Yani Pratiwi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The reception of health logistics represents a critical initial stage that determines the quality and safety of pharmaceutical preparations, medical devices, and medical consumables prior to their use in patient care. This study aims to analyze the implementation of health logistics reception procedures at PSJ, PT, and PP Pharmacies in Makassar City based on the Pharmaceutical Service Standards outlined in Ministry of Health Regulation Number 73 of 2016. An observational design with a descriptive quantitative and evaluative approach was employed through direct observation and interviews with the Pharmacist in Charge and relevant personnel. Data were collected using a checklist comprising nine reception indicators and analyzed using percentage calculations based on the Guttman scale. The findings show that all pharmacies consistently and comprehensively executed every required procedure. Each facility achieved the maximum evaluation score of nine out of nine, reflecting a one hundred percent compliance rate categorized as very good. All stages, including physical product inspection, document verification, batch number and expiration date checking, management of discrepancies through return procedures, and administrative validation, were conducted in accordance with regulatory requirements. These results indicate that the managerial aspects of health logistics reception across the three pharmacies are well structured and accurate, ensuring the quality and safety of products prior to patient use. The study recommends regular internal audits and the development of logistics management innovations to maintain and enhance reception performance in subsequent periods.